Caution Ahead: Identifying Red Flag Signs and Symptoms in Patients With Migraine. (October 2022) - Cook, Calli
Abstract : Headache is a commonly encountered symptom in urgent care and the emergency department. Headache syndromes are classified a primary headache and do not require neuroimaging; however, patients should be assessed at each encounter for changes in their headache symptoms. This case highlights a patient who was suffering from a new headache type, characterized as different from her previous attacks and unyielding to her current acute and preventive treatment methods. The patient was sent for neuroimaging and found to have a mass within her sella turcica that required surgical intervention and removal. Assessing headache patients for red flag symptoms can uncover significant alterations in the patient's symptomatology and indicate a need for further evaluation. By evaluating for red flag symptoms, clinicians can ensure the delivery of high-quality care and better health care outcomes for patients with headache disease.